Computational modeling of infectious disease with applications in Python - Csefalvay, Chris von (London, UK San Diego, CA Academic Press, an imprint of Elsevier, 2023)
Computational Modeling of Infectious Disease: With Applications in Python provides an illustrated compendium of tools and tactics for analyzing infectious diseases using cutting-edge computational methods. From simple S(E)IR models, and through time series analysis and geospatial models, this book is both a guided tour through the computational analysis of infectious diseases and a quick-reference manual. Chapters are accompanied by extensive practical examples in Python, illustrating applications from start to finish. This book is designed for researchers and practicing infectious disease forecasters, modelers, data scientists, and those who wish to learn more about analysis of infectious disease processes in the real world.--
Includes bibliographical references (pages 413-438) and index.
Keywords: Medical informatics; Communicable diseases -- Data processing; Communicable diseases -- Mathematical models